Clinical practice guidelines for the prevention, diagnosis and management of infections related with hemodialysis access of the Peruvian Health Social Security (EsSalud) - Hinostroza-Sayas, Juana (2022)
Background: This article summarizes the clinical practice guidelines (CPG) for the prevention, diagnosis and management of infections associated with hemodialysis access of the Peruvian Health Social Security (EsSalud). Objective: To provide clinical recommendations based on evidence for the prevention, diagnosis and management of infections associated with hemodialysis access in EsSalud. Material and Methods: A guideline development group (GDG) was established, including medical specialists and methodologists. The GDG formulated 7 clinical questions to be answered in this CPG. Systematic searches of systematic reviews and primary studies (when pertinent) were conducted in PubMed, and CENTRAL (Cochrane) from November 2019 to March 2020. The evidence was selected to answer each of the clinical questions. The accuracy of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice and the treatment flowchart. Finally, the CPG was approved with Resolution No. 116-IETSI-ESSALUD-2020. Results: The present CPG addressed 7 clinical questions of four topics: prevention, diagnosis and treatment. Based on these questions, 12 recommendations (11 strong recommendations and 1 weak recommendation), 33 points of good clinical practice, and 2 flowcharts were formulated. Conclusion: This paper summarizes the methodology and evidence-based conclusions from the CPG for the prevention, diagnosis and management of infections associated with hemodialysis access of EsSalud.